Dairy vet with global experience. (24th October 2015) - Fishwick, John
Abstract : Having been born into a busy veterinary household, John Fishwick was advised to choose a non‐veterinary career; however, as a teenager he ignored that advice, having decided that a veterinary career would suit him. He has worked in practice in the UK and abroad and is now head of the Department of Production and Population Health at the Royal Veterinary College